Meat quality of young Nellore bulls with low and high residual feed intake - Zorzi, K.; Bonilha, Sarah Figueiredo Martins; Queiroz, A. C.; Branco, R. H.; Sobrinho, T. L. [UNESP]; Duarte, M. S. (Elsevier, 2013)
Fifty-nine Nellore bulls from low and high residual feed intake (RFI) levels were studied with the objective of evaluating meat quality traits. Animals were slaughtered when ultrasound-measured backfat thickness reached 4. mm, and samples of Longissimus were collected. A mixed model including RFI as fixed effect and herd and diet as random effects was used, and least square means were compared by t-test. More efficient animals consumed 0.730. kg dry matter/day less than less efficient animals, with similar performance. No significant differences in carcass weight, prime meat cuts proportion, chemical composition, pH, sarcomere length, or color were observed between RFI groups. Shear force, myofibrillar fragmentation index and soluble collagen content were influenced by RFI, with a higher shear force and soluble collagen content and a lower fragmentation index in low RFI animals. Feedlot-finished low RFI young Nellore bulls more efficiently convert feed into meat, presenting carcasses within quality standards. © 2012 Elsevier Ltd.
Keywords: Beef; Beef cattle; Carcass; Feedlot; Tenderness; Chemical compositions; Fragmentation index; Quality standard; Significant differences; Animals; Collagen; Meats; collagen; animal; animal food; body weight; caloric intake; cattle; color; diet; male; meat; mechanical stress; metabolism; muscle fibril; regression analysis; sarcomere; skeletal muscle; standard; Animal Feed; Animal Nutritional Physiological Phenomena; Body Weight; Cattle; Color; Diet; Energy Intake; Least-Squares Analysis; Male; Meat; Muscle, Skeletal; Myofibrils; Sarcomeres; Stress, Mechanical